Dati skozi ali prestati? - Gantar, Polona (Sodobna pedagogika, 2025)
This paper describes the difficulties students encounter when using multiword expressions (MWEs) in independent text production. Our analysis is based on teachers‘ corrections in the Developmental corpus Šolar 3.0 (Arhar Holdt et al. 2022) and linguistic decisions made during the development of the evaluation dataset for automated error correction Šolar-Eval (Gantar et al. 2023). We categorize the identified issues in the use of MWEs according to the type of alternative linguistic expression (formal, lexical, and contextual; Geeraerts 1994), the type of MWE (fixed expressions, phraseological units, collocations, syntactic constructions), and whether the expression is a variant or an error. Language allows multiple ways of expressing the same idea, which means that corrections are not always unambiguous. At the same time, the spectrum of MWE issues ranges from errors – relatively rare occurrences that lead to misunderstanding, misinterpretation, or unexpected choices from a native speaker‘s perspective, to variants, where an alternative phrasing of the same message exists. Recognizing these different expressions enables the formulation of feedback that offers not only more correct, stylistically appropriate, and collocationally suitable phrasing but also alternative expressions that in the language function more or less equivalently. In school writing, there is a noticeable intentional use of more expressive linguistic choices to enrich the text and enhance narrative vividness, whereas teacher‘s corrections tend to favor more neutral expressions and simplification (e. g., go through – endure).
Keywords: collocations; correction of school texts; frazeološke enote; jezikovna napaka; jezikovna varianta; kolokacije; language error; linguistic variation; multiword expressions; phraseological units; popravljanje šolskih besedil; povratna učiteljska informacija; sintactic combinations; skladenjske zveze; teacher‘s feedback; večbesedne enote